Editorial note: Welcome to the year 2023 and Volume 26 - Are we ready for the next disaster? - Assounga, Alain G (African Journal of Nephrology, 2023)
On behalf of the Editors and the Editorial Board of the African Journal of Nephrology (AJN), I wish all authors, reviewers and readers a blessed and prosperous New Year! I wish to express my sincere gratitude to Prof Fergus Caskey, for his great contribution to AJN as Associate Editor. He left the Journal last year. We wish him great success in his new and future endeavours. I am proud of the AJN publications for Volume 25, published last year. Indeed, AJN is progressing very well to establish itself as the journal of choice for publishing African nephrology research. In 2022, we published three excellent reviews covering hyperuricaemia in chronic kidney disease, the measurement of GFR in Africa and a road map for kidney care in Africa. Eighteen original articles from diverse African countries were also published last year. We were pleased to publish the 2020 annual report for the South African Renal Registry, and we call on other African countries to submit their registry reports for publication. The international community has decreed that this year’s World Kidney Day theme is: “Kidney health for all, preparing for the unexpected, supporting the vulnerable.” This theme is pertinent and should assist with the progress toward the “Health for all” goal. In nephrology, the unexpected can be very expensive. From the management of hypovolaemia to dialysis in acute kidney injury, how ready are we? At an individual level, a family level, societal level, regional level, country and continental level and finally, at a global level, we need to prepare to deal with disasters. Countries often rely on NGOs such as Médecins Sans Frontières, Gift of the Givers and others to do the work. We should commend these NGOs for their assistance. In Africa, government institutions need to improve their capacity for disaster management. The nephrology community in Africa, through AFRAN, could play a significant role together with other regional organisations. This role will require a commitment like the one we proposed in a book we published ten years ago, “Kidney disease in an African setting” [1]. The closest community to the disease must take the lead, as time is of the essence. I am encouraged by the level of cooperation in AFRAN during the COVID-19 pandemic, which produced guidelines for managing COVID-19 in Africa [2]. We should emulate that effort as a legacy of the COVID-19 experience and use the AFRAN committee structures to put together projects that bring positive progress to kidney care in Africa. I propose that this initiative be named the Antony Were COVID Legacy initiative, inspired by and in honour of our AFRAN President, who started the revival of AFRAN during the COVID-19 pandemic but could not live to witness the end of it. On a lighter note, we all remember our collective dedication during the long Sunday evening AFRAN meetings chaired by Dr Were. Let us commit ourselves to his memory and in memory of all our colleagues who lost their lives to COVID-19. Alain G Assounga Editor-in-Chief